Enhanced Nutritional and Functional Recovery in Femur Fracture Patients Post-Surgery: Preliminary Evidence of Muscle-Targeted Nutritional Support in Real-World Practice - Francisco José Soria Perdomo; Sara Fernández Villaseca; Cristina Zaragoza Brehcist; Elena García Gómez (Geriatrics)
Background/Objectives: To describe the effects of muscle-targeted oral nutritional supplementation (MT-ONS) on nutrition, functional capacity, and other health outcomes in patients after femur fracture surgery. Methods: A prospective, open-label, single-centre study was conducted. Patients aged 80+ post-femur fracture were recruited. They were assessed at baseline and after 90 days with MT-ONS, 100% whey protein enriched with leucine and vitamin D. Demographics, clinical and nutritional status (MNA®-SF), functional capacity [Barthel Index (BI), Lawton and Brody (LB) scale], muscle strength (dynamometry), cognition [Global Deterioration Scale (GDS)], tolerability, and satisfaction data were collected. Descriptive statistics were performed. Ethical approval was obtained. Results: Thirty-one patients (74% women, mean age 87 ± 3.99 years) were enrolled. At baseline, 32% were malnourished and 65% were at risk. After ≥90 days of MT-ONS, malnutrition decreased to 13% and well-nourishment increased to 32%. Ninety percent gained weight, with significant muscle strength improvements (+2 kg, p < 0.001). Eighty-one percent achieved a BI score ≥ 60 points [mean 84.8 (±17.82)]. BI score improvements correlated with higher baseline muscle strength (rho = 0.413, p = 0.021) and better nutritional status (rho = 0.464, p = 0.009). The mean LB score was 4.84 (±2.26). Improvements correlated with the pre-fracture BI score (rho = 0.475, p = 0.007). Positive correlations were noted between nutritional status, muscle strength, and functional outcomes. Cognition remained stable (GDS = 1 in 67.7% patients). Tolerability and satisfaction with MT-ONS were high at 90%. Conclusions: MT-ONS, 100% whey protein enriched with leucine and vitamin D, for ≥90 days enhances nutritional status and functional recovery in patients after femur fracture surgery.